Recent Advances in the Application of Nanometal Catalysts for Glaser Coupling - Ebrahimiasl, Saeideh; Behmagham, Farnaz; Abdolmohammadi, Shahrzad; Kojabad, Rahman N.; Vessally, Esmail (Current Organic Chemistry, 2019)
Synthesis of symmetrical 1,3-diynes from terminal alkynes through an oxidative process is generally called Glaser coupling. The classic Glaser coupling is catalyzed by copper salts under an atmosphere of molecular oxygen as an oxidant. Over the past years, different metal catalysts and oxidants were successfully used in this atom economical C-C coupling reaction. Moreover, several procedures for the preparation of unsymmetrical 1,3-diynes by coupling two different alkyne substrates have been developed. In this review, we will highlight the usefulness of transition metal nanoparticles as efficient catalysts in homo- and hetero-coupling of alkynes by hoping that it will be beneficial to the development of novel and extremely efficient catalytic systems for this fast-growing and important reaction.
Keywords: terminal alkynes